Development Of A Framework And A Model On Disaster Risk Reduction For Science Teacher Professional Development In Biliran Province, The Philippines - Canlas, Ian Phil Canlas (2021)
The increasing number, intensity, and unpredictability of natural hazards all over the world has increased the call and consensus to integrate disaster risk reduction in existing school curricula such as the science curriculum of the Philippine basic education programme. Considering that disaster risk reduction is an emerging concern, it brings a number of opportunities and challenges in the education sector including public schools. This multiphase study was aimed at developing a model of a science teacher professional development on disaster risk reduction for public school teachers in Biliran Province, the Philippines. Study 1 attempted to explore the implementation of disaster risk reduction in schools specifically the integration and teaching of disaster risk reduction in science from grades 3 to 10 through document analysis of key curriculum documents and interviews of key stakeholders including the disaster risk reduction coordinator, school principals, science teachers, and students whose selection was guided by the theoretical sampling principles of the Grounded theory. Informed by the results of Study 1, Study 2 attempted to measure the influence of technological, pedagogical, and content knowledge, as well as values, beliefs, and norms on teaching disaster risk reduction from among 189 science teachers selected through cluster sampling. Results of Study 2 together with existing guidelines from the Department of Education informed Study 3 that attempted to develop a contextualized model of a science teacher professional development on disaster risk reduction through Delphi process participated by ten purposively selected experts